Poster: Context aware route determination model for mobile indoor navigation systems for vision impaired people - Fernando, N.; McMeekin, David; Murray, Iain (2016)
© 2016 Copyright the author(s). Way finding abilities of vision impaired (VI) people cannot be expected to be as same as that of people who use the vision as the primary sense so the route determination methods in travel AIDS for VI people needs to adopted accordingly. This study proposes an indoor route determination model which considers the built environment and user context as the priority factors instead of the distance. It will identify how the elements of a built environment affect the determination of a suitable path which maximizes safety and convenience in an unfamiliar environment and how this path does varies with the individual characteristics of VI people.